Foveal Damage Due to Subfoveal Hemorrhage Associated with Branch Retinal Vein Occlusion - Muraoka, Yuki (PLoS One, 2015)
To investigate the functional and morphologic prognoses of eyes with subfoveal hemorrhage from acute branch retinal vein occlusion (BRVO), and to examine the effect of intravitreal ranibizumab injection (IVR) on these prognoses, we assessed 81 eyes with acute BRVO, of which 38 did not receive IVR [IVR(-) group], and 43 were treated with IVR [IVR(+) group] for macular edema. The foveal morphologic changes were examined via optical coherence tomography (OCT). At initial examination, 63 eyes exhibited subfoveal hemorrhage. At final examination, the defect lengths in the foveal external limiting membrane (ELM) and ellipsoid lines in these eyes were longer, and final VA was significantly poorer, compared with eyes without subfoveal hemorrhage. In comparisons between the final measurements in eyes with subfoveal hemorrhage in the IVR(-) and IVR(+) groups, while there were no differences in initial ocular conditions, final VA was significantly better in the IVR(+) group. The defects in the ELM and ellipsoid lines in the IVR(+) group were shorter than those of the IVR(-) group (p = 0.002 in both). Final VA was correlated with the defect lengths of foveal ELM and ellipsoid lines in both the IVR(-) and IVR(+) groups (both p < 0.001). In addition, the defect lengths of foveal ELM and ellipsoid lines were closely correlated with the duration of subfoveal hemorrhage (both p < 0.001). BRVO-associated subfoveal hemorrhage caused damage to the foveal photoreceptors, and visual dysfunction. However, IVR improved these prognoses, by accelerating the absorption of the subfoveal hemorrhage.